2017
DOI: 10.1063/1.4990487
|View full text |Cite
|
Sign up to set email alerts
|

High repetition rate, multi-MeV proton source from cryogenic hydrogen jets

Abstract: We report on a high repetition rate proton source produced by high-intensity laser irradiation of a continuously flowing, cryogenic hydrogen jet. The proton energy spectra are recorded at 1 Hz for Draco laser powers of 6, 20, 40, and 100 TW. The source delivers ∼1013 protons/MeV/sr/min. We find that the average proton number over one minute, at energies sufficiently far from the cut-off energy, is robust to laser-target overlap and nearly constant. This work is therefore a first step towards pulsed laser-drive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 41 publications
0
53
0
Order By: Relevance
“…With petawatt lasers at shot rates that are of the order of 10 Hz for ELI-BL [383] , and with a petawatt system at ELI-ALPS running at 10 Hz and a terawatt system running at 100 Hz [384] , there is at least two orders of magnitude increase in the number of targets that can be shot; currently there is insufficient capacity to manufacture enough targets using conventional techniques. To overcome this challenge, high-repetition-rate liquid targets have been proposed [385][386][387] , and recently there has been a demonstration of multi-MeV proton acceleration from sub-micron liquid sheet targets at 1 kHz repetition rates [388] .…”
Section: Plasma Diagnosticsmentioning
confidence: 99%
“…With petawatt lasers at shot rates that are of the order of 10 Hz for ELI-BL [383] , and with a petawatt system at ELI-ALPS running at 10 Hz and a terawatt system running at 100 Hz [384] , there is at least two orders of magnitude increase in the number of targets that can be shot; currently there is insufficient capacity to manufacture enough targets using conventional techniques. To overcome this challenge, high-repetition-rate liquid targets have been proposed [385][386][387] , and recently there has been a demonstration of multi-MeV proton acceleration from sub-micron liquid sheet targets at 1 kHz repetition rates [388] .…”
Section: Plasma Diagnosticsmentioning
confidence: 99%
“…A hydrogen droplet source for application in laser-plasma physics was developed by Costa Frage et al [15]. In the framework of laser-driven particle acceleration Gauthier et al [16,17] used a jet for the purpose of accelerating protons, while a further investigation of the target-geometry dependence was studied by Obst et al [18]. A drawback of these kind of structures like droplets, jets or ribbons is on the one hand the position stability as e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A drawback of these kind of structures like droplets, jets or ribbons is on the one hand the position stability as e.g. discussed in [17], where the spatial jitter overcomes the diameter of the target. On the other hand, this goes along with the general requirement to align and focus the laser reliably onto a specific position in space.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been demonstrated that cryogenic hydrogen jets 3 allow for studies of electron-ion equilibration 4 and the generation of pulsed proton beams. [5][6][7] The reliable shot-to-shot characterization of jet thickness, pointing jitter, relative alignment with tiny laser foci and potentially the time-resolved probing of the hydrodynamic plasma expansion, calls for high-resolution a) ulf.zastrau@xfel.eu single-shot imaging with sub-micrometer resolution. Static, time-integrating microscopy in the sub-µm regime has already demonstrated the advantage of extreme ultraviolet (EUV) radiation using transmissive 8 and reflective optics.…”
Section: Introductionmentioning
confidence: 99%